Sense of Magnitude - Trivedi, Nripesh (International Journal of Scientific Research and Management (IJSRM), 2024)
It is often wondered what is the pattern followed by numbers everywhere. This has applications from science to daily routine of people. This paper answers this problem. In this paper, a simple but accurate sense of numbers or magnitude is presented.